Re-visiting sustainable development: sustainability and well-being from the perspectives of indigenous people in rural Ghana. Issue 3 (4th March 2022) - Derbile, Emmanuel Kanchebe; Atanga, Raymond Aitibasa; Abdulai, Ibrahim Abu
ABSTRACT: Although the Brundtland Commission's definition of Sustainable Development (SD) is widely accepted and central to the Sustainable Development Goals (SDGs), it presents some limitations for application in the traditional African context. Drawing on a qualitative research design, this study interrogated indigenous knowledge systems of land governance among the Grune people in northern Ghana and the implications for SD. The emergent perspectives on land and land ownership are compelling and underpin the need for re-conceptualisation SD. To adapt SD to Grune worldview, it is imperative to redefine the frontiers of SD, by embracing a three-generational framework for addressing needs and achieving total wellbeing. In the context of decentralisation in Africa, an Endogenous Development (ED) approach to development planning is imperative for engineering social innovations and learnings that ensure socially and culturally acceptable development and the well-being of indigenous people and communities.